Analisis Kebutuhan ICT dalam Pengajaran Matematika untuk Meningkatkan Literasi Digital Siswa di Indonesia - Firmansyah, Ricky (Indo-MathEdu Intellectuals Journal, 2025)
Technology enables mathematics teaching to be more interactive, visual, and flexible, which can enhance the understanding of complex mathematical concepts. This study aims to analyze the need for information and communication technology (ICT) in mathematics education to improve students' digital literacy in Indonesia. In the rapidly advancing digital era, the integration of ICT in learning is crucial to preparing students for future challenges. This research employs a Systematic Literature Review (SLR) methodology to analyze the literature on the use of ICT in mathematics education. The data sources for this study are secondary data from various relevant studies. Data were obtained from trusted sources such as Google Scholar, Scopus, and JSTOR, and then analyzed using a thematic approach. The findings indicate that while ICT can provide significant benefits, policies that support technological infrastructure improvements and teacher training are necessary. Additionally, students' motivation to use technology in learning should also be considered to make the mathematics learning process more effective. This study provides valuable insights for the development of educational policies and technology-based mathematics teaching practices in Indonesia